Some questions of the application of library management - Tofiq, Rzayeva Zahida; Oqlu, Mammadov Mehmanali Akbar; Kazimi, Parviz Firudin Oqlu (Technium Social Sciences Journal, 2022)
Management is also a way of specific and expedient organization of socio-economic relations, a process that provides a link between individual parts and elements of an integral system. Management is a means of purposeful influence on a specific object in order to achieve a predetermined and conscious goal, to achieve a result. In addition, as a result of the application of management, its principles and methods in many sociocultural areas, including libraries, a new concept of library work has emerged, namely the concept of library management. Library management - in order to manage the work of the library at the level of the requirements of the time, using the labor, intellectual and behavioral motives of the library staff, applying advanced methods of work and methods proven in the world theory and practice of management, in order to achieve the goals set for the library is a related field of professional activity . The article explains the concept of management and shows that this system of activity takes into account the process of self-management, organization of activities, distribution of functions and responsibilities between performers, efficient selection and use of resources, adoption of multivariate decisions and the presence of other similar issues. It also notes that as a result of the application of a number of management methods in libraries, a new concept of library management has emerged - library management. The research paper provides details on this concept.